2016
DOI: 10.1177/0333102416631282
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-responsive painful ophthalmoplegia: Tolosa–Hunt syndrome, Eales disease, or both?

Abstract: Introduction Tolosa-Hunt syndrome (THS) is one of the most common 'benign' causes of painful ophthalmoplegia. Diagnosis is based on clinical and imaging findings and the exclusion of other causes because there is no specific biomarker for the syndrome. Eales disease, an idiopathic inflammatory venous disease that primarily affects the eye, can also affect the central (as stroke or myelitis) and peripheral nervous system. Case report We report the case of a 32-year-old woman with a subacute left ophthalmoplegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…neoplasms) [2]. Mendonca et al reported a case in which an initial diagnosis of THS was later revealed to be Eales disease during the follow-up [14]. Similarly, Brandy-Garcia et al reported a case of a 55-year-old woman presenting THS symptoms, who was diagnosed with sarcoidosis after additional testing [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neoplasms) [2]. Mendonca et al reported a case in which an initial diagnosis of THS was later revealed to be Eales disease during the follow-up [14]. Similarly, Brandy-Garcia et al reported a case of a 55-year-old woman presenting THS symptoms, who was diagnosed with sarcoidosis after additional testing [15].…”
Section: Discussionmentioning
confidence: 99%
“…Mendonca et al . reported a case in which an initial diagnosis of THS was later revealed to be Eales disease during the follow-up [ 14 ]. Similarly, Brandy-Garcia et al .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed ophthalmological examination should not complemented without fluorescein angiography to exclude Eales' disease which is steroid responsive vasculopathy PO mimicking THS, specifically retinal or optic disc neovascularization, peripheral venous leakage, oedematous macular area, perivasculitis of the retina and non-perfused areas should be examined [57]. Slit-lamp examination for the inspection should be done to preclude the possibilities of sclerokeratitis bilaterally and optic atrophy as manifestation of Takayasu's arteritis (TA) which may mimick THS by 6th and 7th CNs palsies and corticosteroid responsiveness, hence confirmatory CT aortic angiography should be ordered [58].…”
Section: Physical Examintion/signsmentioning
confidence: 99%
“…Therefore, it has been suggested that Tolosa-Hunt syndrome should be made a diagnosis of exclusion, since the MRI can be normal. Another aspect of the differential diagnosis of Tolosa-Hunt syndrome is that other entities or syndromes exist that might also mimic Tolosa-Hunt syndrome, such as Eales disease (23) and Gradenigo syndrome (24).…”
Section: Diagnostic Considerationsmentioning
confidence: 99%